Gender dan Politik: Analisis Rendahnya Keterwakilan Perempuan dalam Seleksi Bawaslu RI - Hapsari, Raissa Kusuma; Ilmar, Anwar (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
This research aims to investigate the factors that cause the low representation of women in the recruitment of prospective members of the Bawaslu RI for the 2022-2027 period. The problem in this research is related to the recruitment of prospective members of Bawaslu RI for the 2022-2027 period who have not met the 30% quota for women's representation as mandated in Law No. 7 of 2017 and will be analyzed using the theory of supply and demand model of candidate selection by Norris and Lovenduski.  This research uses qualitative research methods using primary and secondary data sources. This research found that the low representation of women in the recruitment process was caused by the supply and demand sides. On the supply side, it was found that women still lack preparedness regarding time, financial resources, support networks, and motivation. Of all the resources women have, support network resources are the most influential in achieving a position as a member of Bawaslu RI. Next, on the demand side, it was found that work background, education, gender, and age were not selectors' preferences when selecting prospective members of the Bawaslu RI. It was found that the recruitment system was not based on gender justice because the political process still took into account male aspects. This research has urgency for the world of politics and elections, namely, to create a recruitment process in election organizers that is transparent, accountable and in favor of women.